Analysis of Loss Allocation in Radial Distribution Systems Incorporating Distributed Generation (International Journal of Scientific Research in Science and Technology, 2025)
This explores Distribution Loss Allocation for Radial Systems Including Distributed Generators (DGs), focusing on the application and comparison of four different loss allocation methods: Pro Rata, Marginal, Z-bus, and branch current decomposition method (BCDM). The primary objective is to calculate and allocate transmission losses among generators and consumers in a radial distribution network, particularly in the presence of DGs. The Pro Rata method, although simple, allocates losses proportionally but lacks precision in complex systems. The Marginal method improves allocation by considering the marginal cost of losses, offering more equitable results. The impedance-bus (Z-bus) method, using network impedance, provides a detailed approach to account for the topology and placement of generators, making it well-suited for systems with DGs. The BCDM method compensates for flow deviations and is effective in systems where power flows are influenced by network constraints and DGs. The results highlight that while the Pro Rata method is suitable for simpler systems, more advanced methods like Marginal, Z-bus, and BCDM offer more accurate and fair loss allocations, ensuring a more equitable distribution of transmission losses in modern power systems with distributed generation.